2021
DOI: 10.3390/jcm10235514
|View full text |Cite
|
Sign up to set email alerts
|

Dysautonomia and Implications for Anosmia in Long COVID-19 Disease

Abstract: Long COVID-19 patients often reported anosmia as one of the predominant persisting symptoms. Recent findings have shown that anosmia is associated with neurological dysregulations. However, the involvement of the autonomic nervous system (ANS), which can aggregate all the long COVID-19 neurological symptoms, including anosmia, has not received much attention in the literature. Dysautonomia is characterized by the failure of the activities of components in the ANS. Long COVID-19 anosmia fatigue could result fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…In the literature, there is no direct report available on the loss of these chemical senses in obese COVID-19 patients. However, the association between obesity and impairment of the oro-naso-sensory perception was reported in the literature [15]. Krams et al (2020) suggested that the obesity paradox provides a possible explanation for the observed population differences in COVID-19 infection and mortality rates between Europe, the USA, and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there is no direct report available on the loss of these chemical senses in obese COVID-19 patients. However, the association between obesity and impairment of the oro-naso-sensory perception was reported in the literature [15]. Krams et al (2020) suggested that the obesity paradox provides a possible explanation for the observed population differences in COVID-19 infection and mortality rates between Europe, the USA, and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether infection-associated dysautonomia is the direct result of the action of the virus on autonomic nervous system (ANS) structures or a consequence of postinfectious immune-mediated processes ( 34 , 35 ).…”
Section: The Role Of Dysautonomia In the Clinical Course Of Covid-19mentioning
confidence: 99%
“…These constellations of symptoms may persist chronically and are termed "Long COVID", or formally, post-acute sequelae of SARS-CoV-2 (PASC) infection [3]. The incidence of PASC is 30% in symptomatic and 5% in asymptomatic patients with COVID-19 infection [4]. Compared to influenza, COVID-19 is reported to be associated with a higher prevalence of anosmia (53% vs. 17%) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to influenza, COVID-19 is reported to be associated with a higher prevalence of anosmia (53% vs. 17%) [5]. PASC patients with or without hospitalization have often reported anosmia and dysgeusia as one of the predominant and persisting symptoms [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation